Structural components of core indicators of development domestic insurance market - Загорська, Дар'я Михайлівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
Helded the analysis of the main indicators of development of the domestic insurance market and their structural components that determine the individual areas of insurance: personal insurance, property insurance, liability insurance and compulsory insurance. Disclosed reciprocity dynamics between rows of data series on structural components of the main indicators of the development insurance market. Identified richness further development of the domestic insurance market.